What can sociologists of globalization and development learn from Nicos Poulantzas?. (October 2019) - Mueller, Jason C.
Several decades ago scholars studying the state, political economy, and power relations were obliged to engage with the ideas of Nicos Poulantzas. Today, his ideas are hard to find in most sociological theorizing—particularly in the United States. This trend is unfortunate, but not unavoidable. This article proposes that we reconsider the insights of Poulantzas as well as the growing community of scholars building a neo-Poulantzasian approach for studies on international politics, economics, and the state. I discuss Poulantzas's prescient but often neglected work on the internationalization of capital and nation-states, along with his theoretical approach to studying the state as a social relation. After highlighting their significance I focus on several neo-Poulantzasian analytical concepts that have extended his insights in creative ways. I argue that Poulantzas and contemporary neo-Poulantzasians offer ideas that are ripe for exploration, elaboration, and incorporation into multiple burgeoning and interrelated areas of inquiry for sociology and beyond. These include studies on the political-economy of development, studies on internationalization and its effect on national-level governance, and studies of the state in the (semi-) periphery. If successful, this article will provoke scholars to engage in innovative transdisciplinary research grounded in the unique and underexplored theories of Nicos Poulantzas.